Role of surface activity in mechanism of actions of tricyclic antidepressants - Nagappa, A.N.; Kole, P.L.; Pandi, P.V.; Shanmukha, I.; Girish, K.; Mishra, R.P.K. (2003)
The role of surface activity has been studied in the mechanism of action of tricyclic antidepressants (TCAs). TCAs have been shown to generate liquid membranes in series with a supporting membrane by the virtue of their amphiphillicity. Transport of important biogenic amines (adrenaline, nor-adrenaline, dopamine and 5-hydroxy tryptamine) and ions (potassium, sodium and calcium) have been studied in the presence of liquid membranes generated by surface-active TCAs. The data on the modifications in the permeability of important biogenic amines and ions indicates that the liquid membranes generated by TCAs may play a significant role in the mechanism of their anti depressant action. The surface-active nature of the drugs has been discussed with relevance to their pharmacological effects. (C) 2003 Elsevier B.V. All rights reserved.